‘’TO ANALYSES SPECTRUM OF ANEMIA IN PATIENTS WITH CHRONIC KIDNEY DISEASE (CKD) AND TO CORRELATE IT WITH THE STAGE OF THE DISEASE.’’ - Dr Satyam Chaurasia; Dr Suvriti Chaurasia (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background- Chronic kidney disease (CKD) is a major global public health problem, estimated to affect more than 10% of the general adult population and up to 50% of some high-risk subpopulations, such as the elderly, those with non-communicable diseases (NCDs), including type 2 diabetes mellitus (T2D) and hypertension, and communicable diseases (CDs), including HIV/AIDS. Aims- To analyses spectrum of anemia in patients with chronic kidney disease (CKD) and to correlate it with the stage of the disease. Materials and methods- This was a prospective study done over one and half year (March 2021- Aug 2022) at NSCB Medical College & hospital, India in 256 CKD patients. The study included adult CKD patients [estimated glomerular filtration rate (eGFR) of 60 mL/min/1.73 m2, who underwent anemia evaluation. The eGFR was calculated from serum creatinine levels using the abbreviated Modification of Diet in Renal Disease equation. Anemia was defined as hemoglobin concentration <13.0 g/dL in males and <12.0 g/dL in females. The anemia was evaluated by RBC count; MCV; MCHC. Kidney function was evaluated using blood urea, and serum creatinine and GFR. The GFR was estimated using MDRD study equation. Results- Out of 256 CKD patients, 46 patients (18%) had microcytic hypochromic anemia while majority of the patients (82%) had normocytic normochromic anemia. Mean age of the patients was 44.83 in patients diagnosed with microcytic anemia while in normochromic anemia mean age was 45.31 with non significance difference statistically. Majority of the patients (64.5%) with CKD were male. Majority of the patients with CKD were associated with profession of private sector employment, farmer, housewife and shopkeeper. The chief complaint in majority of the CKD patients (86%) was weakness followed by fever (14%). By anemic type the complaints in both the groups were not statistically significant (p>0.05). Only 3 patients out of 256 CKD patients had positive family history of normocytic normochromic anemia with insignificant difference statistically. In present study those patients with advanced stage of CKD (stage 5) had a significant association with anemia. Conclusions- Chronic Kidney Disease is a major health problem worldwide. Chronic Kidney Disease leads to a wide range of systemic derangements. Anemia is a very common manifestation among patients of CKD. As the renal dysfunction increases in severity, there is proportional increase of prevalence and severity of haematological impairment. Anemia is a leading cause of morbidity in patients with CKD and it worsens with the stage of the disease. The most common type of anemia is normocytic normochromic anemia due to EPO deficiency and microcytic hypochromic anemia due to iron deficiency. Evaluation of Hb and RBC parameters in patients with CKD helps in classifying the type of anemia and aids in choosing the correct treatment modalities and avoids unnecessary iron overload in the patients.